OBSTACLES IN DETERMINING RESEARCH TITLE FACED BY THE STUDENTS OF ENGLISH STUDY PROGRAM AT UKI TORAJA - Dorkas; Arrang, Judith Ratu Tandi; Siumarlata, Viktor (Teaching English as a Foreign Language Overseas Journal, 2024)
Obstacles In Determining Research Title Faced by The Students of English Study Program at UKI Toraja. The objective of the research is to know the obstacles are experienced faced by the Students of English Study Program at UKI Toraja in determining research titles. The researcher used quantitative method to analyze the data. The participants of this study were students at UKI Toraja in the academic year 2023/2024. To collect data, the author used the Likert scale quantitative method. This research found that there are still many students who experience obstacles in determining research titles, are: facing obstacles related to interest, academic ability, literature limitations, personal motivation, uncertainty of topic relevance, time limitations, lack of knowledge, resource limitations, and lack of ideas or inspiration in determining the title of their research. Based on the result above, it can be concluded that in determining research titles, especially for English students, there are still many obstacles that they experience as mentioned above.